Prevalance And Incidence Rate Of Anorectal Malformations In Newborns - Asrapia Hubaisying; Baharuddin, Baharuddin; Fitriyah Idrus (Jurnal EduHealth, 2024)
Anorectal malformations (MAR) are significant congenital abnormalities in newborns, requiring early detection and prompt treatment to prevent serious complications and improve prognosis. The aim of this study is to evaluate the prevalence and incidence rate of MAR in Indonesia, identify contributing genetic and environmental factors, and assess the effectiveness of early detection methods and treatment strategies. The research method involved literature review and reference analysis of various MAR-related studies, including epidemiological studies, case reports, and experimental research. The results of the analysis show that the prevalence of MAR in Indonesia ranges from 1 in 5,000 to 1 in 7,000 live births, with risk factors including genetic mutations, exposure to teratogenic substances, and maternal medical conditions. A multidisciplinary approach and psychosocial support are essential for optimal management and improving the prognosis of infants with MAR. In conclusion, a holistic and sustainable approach is needed to address MAR, ensure accurate diagnosis, and provide comprehensive care for affected infants and families.